EFEKTIVITAS PENERAPAN REDD+ DI KALIMANTAN BARAT REGULASI DAN CAPAIAN PENGURANGAN EMISI - NIM. A1012211017, DIMAS GALIH WICAKSANA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The global climate crisis, driven by rising greenhouse gas (GHG) emissions from human activities, poses a severe threat to humanity. Deforestation and land-use change, particularly in forest-rich countries like Indonesia, are major contributors to these emissions. Conflicts over forest management between indigenous communities, government authorities, and private companies further exacerbate the issue. Indonesia, as the world